2003
DOI: 10.1088/0953-8984/16/2/021
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electron holography of biased semiconductor devices

Abstract: Off-axis and in-line electron holography have been used to determine the electrical properties of a silicon p-n junction. Specimens were prepared for transmission electron microscopy (TEM) by focused ion beam (FIB) thinning and examined in a biasing holder, with holograms recorded as a function of specimen thickness and applied reverse bias. The data revealed the important role played by the surfaces of the thin TEM sample which affect the electrostatic potential distribution within the specimen. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The proposed electrostatic 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y 5 potential variation and the separation of crystalline and electrically active membrane thicknesses are consistent with previous reports [9][10][11]. Equation 2 assumes that the external electric field is negligible, that the reference wave passes through unperturbed vacuum and that the electrical properties of the specimen are constant in the beam direction within specimen thickness t el .…”
Section: Tem-based Dopant Profiling Techniquessupporting
confidence: 90%
See 1 more Smart Citation
“…The proposed electrostatic 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y 5 potential variation and the separation of crystalline and electrically active membrane thicknesses are consistent with previous reports [9][10][11]. Equation 2 assumes that the external electric field is negligible, that the reference wave passes through unperturbed vacuum and that the electrical properties of the specimen are constant in the beam direction within specimen thickness t el .…”
Section: Tem-based Dopant Profiling Techniquessupporting
confidence: 90%
“…The experimental results are fitted to simulations to obtain best-fitting parameters for the dopant-dependent electrostatic potential distribution in the specimen. Some of the off-axis electron holography results have been presented in preliminary form elsewhere [10,11]. Figure 1a shows a schematic diagram illustrating the formation of an off-axis electron hologram.…”
Section: Introductionmentioning
confidence: 99%
“…Electron holography in transmission electron microscope (TEM) has been employed to map the depletion layer in p-n junction 14 , the interfacial polarization field in the superlattices 15 , two-dimensional electron gas and twodimensional hole gas in the high electron mobility transistor device 16 and the charge distribution in nanomaterials 17 . Combined with in situ techniques, the bias-induced potential variations in p-n junction 18 and metal oxide semiconductor (MOS) transistor 19 were imaged. It should be noted that electron holography in TEM possesses the merit to snapshot the potential image with high spatial resolution, which is extremely important for the characterization of nanometre materials and devices.…”
mentioning
confidence: 99%
“…However, quantification of the results is complicated by the need to interpret the effect on the potential of Ga ion implantation and damage at the specimen surfaces. Earlier work by Twitchett et al (2002) suggested the presence of 25-nm-thick electrically ''dead'' crystalline layers close to each specimen surface, in addition to amorphous surface layers. The modified crystalline surface layers may result from the generation of point defects by knock-on damage brought about by the 30 kV Ga ion beam, as well as from doping by the Ga ions.…”
Section: Two-dimensional Off-axis Electron Holography Of Semiconductomentioning
confidence: 98%
“…For a semiconductor specimen, both external electrostatic fringing fields and internal potential variations must be taken into account to be able to interpret the observed phase shift quantitatively. The interpretation can be simplified if the external electrostatic fringing fields are absent; for example, if the specimen surfaces are coated with a conductive layer of carbon to provide an equipotential specimen surface (McCartney et al 2002) or if focused ion beam (FIB) specimen preparation is used (Twitchett et al 2002). This possibility is discussed below.…”
Section: Introductionmentioning
confidence: 99%